The Meaning-Enhancing Properties of Psychedelics and Their Mediator Role in Psychedelic Therapy, Spirituality, and Creativity - Hartogsohn, Ido (Frontiers in Neuroscience, 2018)
Past research has demonstrated to the ability of psychedelics to enhance suggestibility, and pointed to their ability to amplify perception of meaning. This paper examines the existing evidence for the meaning-enhancing properties of psychedelics, and argues that the tendency of these agents to enhance the perception of significance offers valuable clues to explaining their reported ability to stimulate a variety of therapeutic processes, enhance creativity, and instigate mystical-type experiences. Building upon previous research, which suggested the potential role of psychedelic meaning-enhancement in enhancing placebo response, the paper explores the mechanisms by which the meaning-amplifying properties of psychedelics might also play a role in enhancing creativity, as well as in effecting mystical-type experiences. The wider social and public-health implications of this hypothesis are discussed, and suggestions are made as to the various ways in which scientific understanding of the meaning-enhancing properties of psychedelics might be advanced and utilized.